2021
DOI: 10.3390/molecules26195849
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Sesamolin: Physicochemical Properties, Pharmacological Activities, and Future Research Prospects

Abstract: Sesame seeds are rich in lignan content and have been well-known for their health benefits. Unlike the other sesame lignan compounds (i.e., sesamin and sesamol), the study of the pharmacological activity of sesamolin has not been explored widely. This review, therefore, summarizes the information related to sesamolin’s pharmacological activities, and the mechanism of action. Moreover, the influence of its physicochemical properties on pharmacological activity is also discussed. Sesamolin possessed neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The COX-2 enzyme activates pain (a symptom of inflammation) mechanisms in the human body. The phytochemical components inherent to sesame seed oil, like sesamol, sesamin, and sesamolin, are responsible for their antioxidant and anti-inflammatory properties [ 37 ]. A clinical trial was conducted to investigate the effect of sesame oil on 40 hypertensive male and female patients aged 35–60 years [ 38 ].…”
Section: Therapeutic Effects Of Eosmentioning
confidence: 99%
“…The COX-2 enzyme activates pain (a symptom of inflammation) mechanisms in the human body. The phytochemical components inherent to sesame seed oil, like sesamol, sesamin, and sesamolin, are responsible for their antioxidant and anti-inflammatory properties [ 37 ]. A clinical trial was conducted to investigate the effect of sesame oil on 40 hypertensive male and female patients aged 35–60 years [ 38 ].…”
Section: Therapeutic Effects Of Eosmentioning
confidence: 99%
“…Secoisolariciresinol, matairesinol, pinoresinol, and lariciresinol are the common lignans from flax seeds and sesamin, sesamoiln, sesamolinol, and sesaminol are the common lignans from sesame seeds [30]. Sesamin and sesamolin possess antioxidant, neuroprotective, and anticancer activities, but sesamol, their decomposition product during the roasting process of sesame seeds (Figure 5), is the major antioxidant of the sesame seeds [31][32][33][34]. The common plant-based phenolic antioxidants are summarized in Table 1.…”
Section: Antioxidants From Plant Sourcesmentioning
confidence: 99%
“…Sesame seed (Sesamum indicum L.) and its oil are popular foods. Previously, sesame oil was found to have protective effects against kidney dysfunction. Notably, sesamolin is a major lignan in sesame oil , and exhibits numerous benefits, including antimelanogenesis, neuroprotective activity, antimicrobial activity, anticancer activity, and enhancement of the cytolytic activity . In addition, experiments on animals have suggested that sesamolin is a potentially strong antioxidant against liver and kidney injuries. However, whether sesamolin can mitigate kidney injury, intestinal barrier dysfunction, and gut microbiota imbalance in high-fat and high-fructose (HF–HF) diet-fed mice is unknown, and the underlying correlations among them need to be further established.…”
Section: Introductionmentioning
confidence: 99%